Representaciones y creencias en torno a la evaluación lingüística del adulto mayor con trastorno cognitivo leve - Valles, Beatriz (Revista de Investigación en Logopedia, 2011)
Given the demographic changes experienced by global population, the attention teams in the area of logopedics are working more and more now with elder patients with a mild cognitive impairment (MCI), that is, people presenting problems of memory and other mental functions, but without them interfering in their daily activities (Speling et. al., 2011). This situation obliges us to develop actions from a new epistemological, ontological and methodological perspective, especially in the developing countries, where people over 65 may face isolation and a lack of public health services, as a result of a series of negative representations around the aging process, which jeopardize their quality of life and determine that the speech and language professional training programs have to tackle topics on aging as a complex and multifactor process. The purpose of this paper is to analyze the social representations to be considered when making a linguistic assessment proposal addressed to the elderly with MCI, from a discursive perspective that can allow the study of the pragmatic components. The use of conversational analysis between patients and key interlocutors as a diagnosis tool and the addition of contents on Psychiatrics, Clinical Linguistics, Geriatrics and Gerontology to the speech and language professional training programs have been proposed as an alternative aimed at achieving a performance adjusted to the complex social frameworks, where the speech and language practice is being currently developed in the developing countries.
Keywords: Elderly; Linguistic assessment; Mild cognitive impairment; Social representations.